Formula of Learning Outcome Soft Skills Under Graduate Midwifery - Yulizawati yulizawati (Universitas Andalas, 2023)
Midwives as women's partners are professions that have jobs with great complexity and responsibility. To achieve access to and quality of good reproductive health, maternal and child health services, fight poverty, improve education, increase the Human Development Index (IPM/HDI) and empower women and gender equality is an important issue to be managed and realized through planned and systematic midwifery education to create a conducive learning atmosphere and learning process so that students actively develop their potential optimally as midwives who have religious spiritual strength, self-control, personality, intelligence, sincerity, noble character, as well as the wisdom and skills needed by themselves, society, nation and country with the ability to develop abilities as a care providers, decision makers, communicators, community leaders and managers, as well as profiles of midwives as life long learners, entrepreneurs and faith and piety. Areas of competence in S1 midwifery education are Effective communication, Legal ethics and patient safety, Self-development and professionalism, Scientific foundation of midwifery practice, Clinical skills in midwifery practice, Health promotion, Management, Leadership and Entrepreneurship in every stage of a woman's life cycle namely Female reproductive health, Pre-marital, Pre-conceptional period, Pregnancy, physiological childbirth and postpartum, Early detection and early management of pathological pregnancy, childbirth and postpartum, Physiological newborns, neonates and toddlers, Early detection and early management of pathological newborns, neonates and toddlers, early detection and early treatment of female reproductive disorders and community midwifery